Gambaran Self-Efficacy Ibu dengan Anak yang sedang menjalani Pengobatan Tuberkulosis di Poliklinik Spesialis Anak Rsud Cibabat Cimahi - Nabilah, Nabilah; Mardhiyah, Ai; Widianti, Efri (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2016)
Introduction: One of important thing of treatment on children tuberculosis is a parent’s existence as a taking medicine guard (PMO) with their roles and tasks. Therefore, it’s important that PMO has a good self-efficacy. The purpose of this research is to describe self-efficacy of mother with children in tuberculosis treatment at paediatric’s polyclinic of RSUD Cibabat Cimahi. Method: The research used descriptive quantitative method with purposive sampling and involving 84 mothers as participant. The data was collected by using closed questionnaire based on self-efficacy theory from Albert Bandura. Results: The result showed that several of participant have a low self-efficacy (53,6%) and the other have a high self-efficacy (46,4%). The result of this research give suggestion to the hospital for creating an appropriate program with phsycosocial approachement , and for nurses, it can be a suggestion that the nurses must give a comprehensive and holistic nursing intervention then doing an accurate nursing intervention, from assessment until the interventions.